Peningkatan Pengetahuan dan Keterampilan Petani Jagung melalui Pelatihan Pembuatan Pupuk Photosynthetic Bacteria (PSB) di Desa Rasau Jaya Satu, Kabupaten Kubu Raya - Singgih Tiwut Atmojo; Irba’ Muhlas Sambodo; Nugra Irianta Denashurya; Nia Permatasari; Gunadi Gunadi; Eko Wahyu Junaidi (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Photosynthetic Bacteria (PSB) provide an environmentally friendly alternative to reduce dependence on chemical fertilizers while improving farmers' knowledge and technical skills in sustainable agriculture. This community service program aimed to enhance the knowledge and practical skills of corn farmers in producing and applying PSB in Rasau Jaya Satu Village, Kubu Raya Regency. The program employed a participatory approach consisting of observation, counseling, demonstrations, hands-on practice, and interactive discussions. Farmers actively learned PSB preparation, application techniques, and its benefits for corn cultivation. The results showed improved participant understanding and practical competence in independently producing PSB using affordable and locally available materials. The training also increased farmers' awareness of environmentally friendly farming practices and encouraged the adoption of sustainable agricultural technologies. Overall, the program demonstrates that participatory training effectively strengthens farmers' capacity, promotes the use of biological inputs as an alternative to chemical fertilizers, and supports the development of sustainable and environmentally responsible corn farming systems.